Review on Globalization and Importance of Strategic Human Resource Management - Alharthey, Dr. Bandar Khalaf (International Journal of Scientific Research and Management (IJSRM), 2018)
Strategic human resource management (SHRM) is the main concern of the managers who are expanding their business at global level. In the current era, recognition of value of the human factor is emphasized by the managers to align business strategy and HR policies. The main purpose of the article is to explore facts about the impact of globalization on HRM with special reference to SHRM. In order to assess these aspects, implications of globalization and SHRM will be analyzed and global orientation of HR professionals will be assessed, so that a deep insight about the importance of SHRM can be developed.